2016
DOI: 10.5858/arpa.2016-0415-ra
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Frozen Section in Thoracic Pathology: Lepidic Lesions, Limited Resections, and Margins

Alain C. Borczuk

Abstract: - Frozen section diagnosis is overall accurate in assessment of lepidic lesions. Pitfalls include rare benign mimickers and more common reactive lesions. Standard approaches to gross assessment and margin measurement require further research with increasing use of lung-sparing resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We also found 44 (21.4%) equivocal or inadequate results with the SIC diagnosis. Thus, we recommend that FSH should be used in addition to SIC for the best qualitative intraoperative diagnosis, except in cases deemed a potential biohazard risk for the pathology staff following SIC, as documented by Sugiyama et al . Nevertheless, intraoperative SIC shows fewer nuclear artifacts than FSH samples, enabling diagnoses of carcinoids or small cell carcinomas to be declared as the final pathological diagnosis during surgery.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We also found 44 (21.4%) equivocal or inadequate results with the SIC diagnosis. Thus, we recommend that FSH should be used in addition to SIC for the best qualitative intraoperative diagnosis, except in cases deemed a potential biohazard risk for the pathology staff following SIC, as documented by Sugiyama et al . Nevertheless, intraoperative SIC shows fewer nuclear artifacts than FSH samples, enabling diagnoses of carcinoids or small cell carcinomas to be declared as the final pathological diagnosis during surgery.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, as shown in Fig. a,b, it is not easy to distinguish invasive mucinous carcinoma from goblet cell metaplasia/hyperplasia by SIC because of the monotonous columnar cells producing a mucinous background in the absence of necrosis, and these characteristics might be interpreted as those of a benign lesion, especially under the time constraints of intraoperative assessment. Also, marked tumor cell necrosis or changes in viable tumor cells due to preoperative chemotherapy could have influenced the results of SIC .…”
Section: Discussionmentioning
confidence: 99%
“…Although the FS can be a precise diagnostic method to guide intraoperative resection procedures for lung adenocarcinoma, it remains difficult to recommend a definitive assessment by FS alone [34]. Borczuk suggested that combining clinical and radiologic information with FS could reduce diagnostic errors [35]. Our results show no significant difference in the AUC values between the FSRV and FSV models, but the former model has better accuracy and calibration.…”
Section: Discussionmentioning
confidence: 54%
“…Considering the performance of radiomics model, we further selected clinical characteristics and frozen section that were strong predictors to build nomogram for predicting LNM.Intraoperative FS was advocated as a useful method for surgical planning, as it could provide more precise diagnosis. Previous studies illustrated that FS combined clinical and radiological features showed good performance and diagnostic accuracy[38][39][40]. Wu et al[39] investigated a CT-based radiomics model and combined it with FS and clinical data to distinguish invasive adenocarcinomas (IA) from preinvasive lesions/minimally invasive adenocarcinomas (PM).…”
mentioning
confidence: 99%